(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Some words you may want to use when meeting or greeting people are “hello,” “goodbye,” and “thank you.” Other words that are commonly used in English for this purpose include “hello,” “good morning,” and “good afternoon.”